UNIVERSAL AND REGIONAL IN INTERNATIONAL LAW ON ENVIRONMENTALLY SUSTAINABLE CITIES (ASEAN AS AN EXAMPLE) - Kopylov Михаил Николаевич; Quang Chien Нгуен (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
The article deals with a comparative legal analyses of the concept of environmentally sustainable cities elaborated by the United Nations Environment Program (UNEP) and the UN – Habitat Program, on the one hand, and within the frame of Association of Southeast Asian nations (ASEAN) – on the other hand. The competence of the ASEAN working group on environmentally sustainable cites, the criteria of sustainability, established in the ASEAN and conditions of nomination on environmentally sustainable city title are disclosed.